2008
DOI: 10.1177/0959683607085607
|View full text |Cite
|
Sign up to set email alerts
|

A record of climate over the last millennium based on varved lake sediments from the Canadian High Arctic

Abstract: where changes are expected to be most extensive, so we need to place these projected changes in the context of past Arctic climate variability. We know, from large-scale studies of climate variability over the last century and the last millennium, and from model simulations, that temperature changes tend to be amplified at high latitudes-and this seems to be true both for the periods of 'natural' and of anthropogenic forcing (Moritz et al., 2002; Holland and Bitz, 2003; Arctic Climate Impacts Assessment (ACIA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 28 publications
(31 reference statements)
5
24
0
1
Order By: Relevance
“…Similarly, Lotter and Birks (1997) examined the thickness of the light and dark layers in the same sequence and explored the effects of nutrients and regional meteorology on seasonal sedimentation. Besonen et al (2008) correlated varve thickness with summer temperatures at an annual resolution for the past millennium. Teranes et al (1999) discussed calcite precipitation in lakes based on geochemical parameters and stable isotopes as well as element ratios of authigenic calcites obtained by sampling of seasonal sediment layers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lotter and Birks (1997) examined the thickness of the light and dark layers in the same sequence and explored the effects of nutrients and regional meteorology on seasonal sedimentation. Besonen et al (2008) correlated varve thickness with summer temperatures at an annual resolution for the past millennium. Teranes et al (1999) discussed calcite precipitation in lakes based on geochemical parameters and stable isotopes as well as element ratios of authigenic calcites obtained by sampling of seasonal sediment layers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, all sufficiently large coastal lakes in the Arctic Archipelago should experience high-conductivity bottom waters (Stewart and Platford 1986). In some freshwater lakes, the annual formation of enriched conductivity water at depth has been noted (Van Hove et al 2006;Besonen et al 2008). At West Lake, Cape Bounty, spring CTD casts reveal bottom waters as high as 0.14 mS cm 21 vs. a column maximum of 0.06 mS cm 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The first main complication arises from the fact that age models are frequently resolved in low time resolution. Nevertheless, annually laminated (varved) sediments yield annually resolved time constrains (Ojala et al 2012), and yet several protocols have been suggested to provide results expressed Petterson et al 1999;Besonen et al 2008). The second complication arises from the density measurement itself.…”
Section: Future Direction: Calibration Of X-radiographs Grey-level Vamentioning
confidence: 99%